Оптимизация программы для решения задачи вытеснения нефти - Касымбек, Н.М.; Мустафин, М.Б.; Иманкулов, Т.С.; Ахмед-Заки, Д.Ж. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Оптимизация программы для решения задачи вытеснения нефти